Growth Response and Results of Two Sorgum Varieties With Different Dosage Application of Arbuscular Mycorrhizal - Mawardhani Munti’ah; Harsono Puji; Supriyono (E3S Web of Conferences, 2023)
Sorghum is an adaptive plant, able to grow and develop on sub-optimal land such as dry land but the soil fertility level is still low. This study aims to determine the variety of sorghum and the appropriate dosage of arbuscular mycorrhizal fungi (AMF) for growing sorghum on dry land and to determine the best interaction effect. Research is carried out in the field and in the laboratory. The environmental design used was a complete randomized block design with two factorials and was repeated three times. The first factor was 2 varieties of sorghum namely Luzhouhong (V1) and Hongyingzi (V2). The second factor was the dose of AMF at a dose of 0 g/plant (D0), 2.5 g/plant (D1), of 5 g/plant (D2), 7.5 g/plant (D3). The results showed that the sorghum variety that had more potential to be developed on dry land based on growth and yield variables was the luzhouhong variety. The right dose of AMF for growth and yield on dry land is a dose of 2.5 g/plant (D1) compared to other AMF doses. The combination of Luzhouhong sorghum varieties with AMF dose of 2.5 g/plant is suitable for development in dry land as a result of seed production.